Association of QT dispersion with mortality and arrhythmic events—A meta‐analysis of observational studies. Issue 1 (11th November 2019) - Bazoukis, George; Yeung, Cynthia; Wui Hang Ho, Ryan; Varrias, Dimitrios; Papadatos, Stamatis; Lee, Sharen; Ho Christien Li, Ka; Sakellaropoulou, Antigoni; Saplaouras, Athanasios; Kitsoulis, Panagiotis; Vlachos, Konstantinos; Lampropoulos, Konstantinos; et al.
Abstract: Background: The risk stratification of coronary heart disease (CHD) and/or heart failure (HF) patients with easily measured electrocardiographic markers is of clinical importance. The aim of this meta‐analysis is to indicate whether increased QT dispersion (QTd) is associated with fatal and nonfatal outcomes in patients with CHD and/or HF. Methods: We systematically searched MEDLINE and Cochrane databases without restrictions until August 15, 2018 using the keyword "QT dispersion". Studies including data on the association between QTd and all‐cause mortality, sudden cardiac death (SCD) or arrhythmic events in patients with HF and/or CHD were classified as eligible. Results: In the analysis including patients with CHD and/or HF, we found that QTd did not differ significantly in patients with SCD compared to no SCD patients while QTd was significantly greater in the group of all‐cause mortality patients and in patients who experienced a sustained ventricular arrhythmia. Subgroup analysis showed that in myocardial infarction studies, QTd was significantly higher in patients with an arrhythmic event compared to arrhythmic event‐free patients while a nonsignificant difference was found in QTd in patients who died from any cause compared to survivors. Similarly, in HF patients, the QTd was significantly greater in patients with an arrhythmic event while a nonsignificant difference was found regarding all‐cause mortality and SCD outcomes. Conclusions: QTd has a prognostic role for stratifying myocardial infarction or HF patients who are at higher risk of arrhythmic events. However, no prognostic role was found regarding all‐cause mortality or SCD in this patient population. Abstract : QTd has a prognostic role for stratifying myocardial infarction or HF patients who are at higher risk of arrhythmic events. However, no prognostic role was found regarding all‐cause mortality or SCD in this patient population.